Effect of the Indium Compositions in Tri-Gate InxGa1−xAs HEMTs for High-Frequency Low Noise Application. (1st November 2022) - Wang, Chun; Kuo, Che-Ning; Lin, Yueh-Chin; Hsu, Heng-Tung; Tsao, Yi-Fan; Lee, Ching-Ting; Chang, Edward Yi
Abstract : In this paper, we investigated the tri-gate Inx Ga1−x As high electron mobility transistors (HEMTs) with different indium compositions for low noise applications. The tri-gate configuration in this work exhibits better device performances of the transconductance (gm ), the current gain cutoff frequency (fT ), the maximum oscillation frequency (fmax ), and the minimum noise figure compared with the conventional planar structure due to the improved gate controllability. The indium contents of 20%, 40%, and 100% tri-gate devices were also fabricated for comparison. The resistances and leakage current were measured to investigate the effect between the indium compositions and the noise figure. Experimental results exhibited that the tri-gate In0.4 Ga0.6 As mHEMT with neither the highest transconductance nor the lowest gate leakage current exhibited the lowest minimum noise figure (NFmin ) of 2 dB when operating at 50 GHz. The study reveals that device architecture and indium composition are important factors in the determination of noise performance.